IMPLEMENTATION OF THE SPECIAL AUTONOMY BUDGET POLICY IN THE FIELD OF EDUCATION IN WEST PAPUA PROVINCE - Mersi Homer; Amy Sri Yayuk Rahayu (JURNAL DARMA AGUNG, 2023)
Policy autonomy special exists from decentralization in Indonesia. Enactment autonomy special for Papua is expected to bring change from side development, enhancement level life public original Papua or so-called OAP, and respect to native rights Papua (OAP) as well as overcome various problems the conflict that occurred. Autonomy special for Papua is regulated in Law Number 21 of 2001 to 2020 or for 20 years, Change second arranged in Law Number 2 of 2021. Education for Indigenous Papuans (OAP) is one regulated aspect of Constitution autonomy specifically Papua as well derivatives. Objective Study This is To know the implementation of autonomy fund policy particularly in the field of Education in West Papua Province, factor inhibitors and supports as well as efforts made to overcome problems that occur. The method research used is descriptive-qualitative. Data collection techniques are carried out with collect data secondary and primary. Whereas technique analysis of research data This uses Edward III's theory where there are four internal variables see implementation wisdom budget autonomy specifically in the field of Education of West Papua Province. Research results based on four internal variables of Edward III's theory ie communication, resources, disposition, and structure bureaucracy show implementation budget autonomy specifically in the field of West Papua Education yet walk with ok. Still, their factors inhibit the implementation of budget autonomy specifically in the field of Education, p This can see from areas that haven't touched development in the field of Education accordingly to the mandate of the autonomy law, especially Papuans.